Ecological aspects of mosquitoes (Diptera: Culicidae) in the gallery forest of Brasilia National Park, Brazil, with an emphasis on potential vectors of yellow fever - Vieira, Ana Raquel Lira (2013)
Introduction: We analyzed the vertical and monthly distributions of culicid species in the gallery forest of Brasília National Park, with an emphasis on the potential vectors of yellow fever (YF). Methods: Between September 2010 and August 2011, mosquitoes were captured on the ground and in the canopy of the forest for five consecutive days per month, from nine to 15 hours. The mosquitoes were examined to verify natural infection with flaviviruses by isolation in Aedes albopictus Skuse, 1864 cells followed by indirect immunofluorescence. Results: We identified 2,677 culicids distributed in 29 species. Most of the mosquitoes were captured at ground level (69%) during the rainy season (86%). The most abundant species were Sabethes (Sabethes) albiprivus Theobald, 1903; Limatus durhamii Theobald, 1901; Haemagogus (Conopostegus) leucocelaenus Dyar & Shannon, 1924; Haemagogus (Haemagogus) janthinomys Dyar, 1921; Aedes (Ochlerotatus) scapularis Rondani, 1848; Psorophora (Janthinosoma) ferox Von Humboldt, 1819; and Aedes (Ochlerotatus) serratus Theobald, 1901. Limatus durhamii, Limatus durhamii, Psorophora ferox, Aedes scapularis and Aedes serratus showed significant differences (p<0.05) in their habitat use. Limatus durhamii was found more often in the canopy, unlike the other species. During the rainy season, the most abundant species were Sa. albiprivus, Haemagogus leucocelaenus and Limatus durhamii. During the dry season, the potential YF vectors exhibited a very low frequency and abundance, except Aedes scapularis and Aedes serratus. No flavivirus was detected in the 2,677 examined mosquitoes. Conclusions: We recommend continued and systematic entomological monitoring in areas vulnerable to the transmission of YF in the Federal District of Brazil.